Contribution and consumption of content in enterprise social media. Issue 1 (2nd January 2018) - Engler, Tobias H.; Alpar, Paul
ABSTRACT: While many enterprises adopt social media to foster collaboration and communication between employees, the question remains whether individual employees adopt it and if so, how they use it. In this study, we distinguish the two major types of use to account for active and passive of social media usage: content contribution and content consumption. Both types of use are modeled as dependent variables in an adapted technology adoption model and tested in a field study.